CTLA-4 +6230G>A polymorphism and its impact on CTLA-4 level and risk of hepatocellular carcinoma: A case-control study in Batak patients with chronic hepatitis B - Darmadi, Darmadi; Rey, Imelda; Lubis, Masrul; Lindarto, Dharma; Muzasti, Riri A. (Narra Sains Indonesia, 2025)
Genetic polymorphisms in cytotoxic T-lymphocyte-associated protein 4 gene (CTLA-4) vary by ethnic background, necessitating population-specific studies. The aim of this study was to assess the association between the CTLA-4 +6230G>A polymorphism, serum CTLA-4 level, and hepatocellular carcinoma (HCC) in Batak patients with chronic hepatitis B, a group with high hepatitis B virus (HBV) endemicity. A case-control study was conducted among cases (Batak patients with chronic hepatitis B and HCC) and controls (chronic hepatitis B without HCC). Genotyping of the CTLA-4 +6230G>A polymorphism was performed using the TaqMan SNP Genotyping Assay. Serum CTLA-4 level was quantified using enzyme-linked immunosorbent assay (ELISA). Patient’s demographic, clinical and laboratory data were recorded and assessed including age, sex, body mass index (BMI), smoking history, cirrhosis status, HBV DNA level, liver function markers (aspartate aminotransferase (AST) and alanine aminotransferase (ALT)), hepatitis B e-antigen (HBeAg) status, smoking history, and alcohol consumption. This study found that G allele was significantly associated with an increased risk of HCC (OR: 2.69; 95%CI: 1.21–6.00; p=0.013). Individuals with GG/AG genotypes had a 2.89-fold higher risk of developing HCC compared to those with the AA genotype (p=0.032). Serum CTLA-4 level was significantly elevated in G allele carriers (GG: 159.9±57.1 pg/mL vs AA: 83.7±44.7 pg/mL; p<0.001). Multivariate analysis identified cirrhosis as the strongest predictor of HCC (OR: 7.60; p<0.001), followed by elevated ALT (OR: 3.42; p=0.018) and high HBV DNA levels (OR: 2.31; p=0.024). In conclusion, the CTLA-4 +6230G>A GG/AG genotype and elevated serum CTLA-4 level were significantly associated with an increased risk of HCC in Batak individuals with chronic HBV infection. Further research is needed to explore additional CTLA-4 polymorphisms and immune regulatory mechanisms in HBV-related HCC to improve risk stratification and therapeutic strategies.